2010
DOI: 10.1007/s11064-010-0158-7
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Handling Impairs Spatial Memory and Leads to Altered Nitric Oxide Production and DNA Breaks in A Sex Specific Manner

Abstract: Early life events lead to behavioral and neurochemical changes in adulthood. The aim of this study is to verify the effects of neonatal handling on spatial memory, nitric oxide (NO) production, antioxidant enzymatic activities and DNA breaks in the hippocampus of male and female adult rats. Litters of rats were non-handled or handled (10 min/day, days 1-10 after birth). In adulthood they were subjected to a Morris water maze or used for biochemical evaluations. Female handled rats showed impairment in spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Finally, enhanced effects of prolonged separation were seen as better reversal learning (Lehmann et al, 1999; Levy et al, 2003). Among studies that report impaired MWM performance, these reflect either increased latency and greater distance to reach the platform (Garner et al, 2007; Huang et al, 2002; Huot et al, 2002; Noschang et al, 2010; Oitzl et al, 2000; Oomen et al, 2010), lower swim distance or time in the former location of the platform during a probe test (Aisa et al, 2009a; Aisa et al, 2009b; Aisa et al, 2007; Brunson et al, 2001; Brunson et al, 2005; Hui et al, 2011; Ivy et al, 2010; Solas et al, 2010), or impaired reversal learning (Ivy et al, 2010; Lehmann et al, 1999; Oitzl et al, 2000). No effect of early life manipulations on MWM was seen in 15 studies (Choy et al, 2008; Gibb and Kolb, 2005; Huot et al, 2002; Ivy et al, 2010; Lai et al, 2006; Oitzl et al, 2000; Oomen et al, 2011; Pryce et al, 2003; Vallee et al, 1999; Vallee et al, 1997).…”
Section: Early Life Stress Effects On Learning and Memory: Spatialmentioning
confidence: 99%
“…Finally, enhanced effects of prolonged separation were seen as better reversal learning (Lehmann et al, 1999; Levy et al, 2003). Among studies that report impaired MWM performance, these reflect either increased latency and greater distance to reach the platform (Garner et al, 2007; Huang et al, 2002; Huot et al, 2002; Noschang et al, 2010; Oitzl et al, 2000; Oomen et al, 2010), lower swim distance or time in the former location of the platform during a probe test (Aisa et al, 2009a; Aisa et al, 2009b; Aisa et al, 2007; Brunson et al, 2001; Brunson et al, 2005; Hui et al, 2011; Ivy et al, 2010; Solas et al, 2010), or impaired reversal learning (Ivy et al, 2010; Lehmann et al, 1999; Oitzl et al, 2000). No effect of early life manipulations on MWM was seen in 15 studies (Choy et al, 2008; Gibb and Kolb, 2005; Huot et al, 2002; Ivy et al, 2010; Lai et al, 2006; Oitzl et al, 2000; Oomen et al, 2011; Pryce et al, 2003; Vallee et al, 1999; Vallee et al, 1997).…”
Section: Early Life Stress Effects On Learning and Memory: Spatialmentioning
confidence: 99%
“…Perhaps the findings observed in the present study might also imply that our deficient diet was able to significantly alter the machinery of antioxidant enzymes. Our group and others have already demonstrated that neonatal handling leads to differences in adolescent and adult rats on neurochemical and behavioral parameters [50][51][52][53][54]73]. We also demonstrated that H and MS, exposed chronically to n-3 PUFAs deficiency, displayed lower brain derived neurotrophic factor protein in hippocampus (BDNF) [20].…”
Section: Discussionmentioning
confidence: 65%
“…This result might be related to an early apoptosis characteristic, maybe induced by oxidative damage. Noschag et al [50] reported that neonatal handled male rats display, when adults, higher DNA break levels in hippocampus, what could be due to oxidative imbalance. Another focus to consider are the possible epigenetics and post translational modifications involved in these processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Noschang et al [38] found that females subjected to an EH paradigm showed impairments in spatial learning, while this effect was not observed in [11, [41][42][43][44]. However, the exact mechanism by which this plasticity occurs remains unclear.…”
Section: Gender As An Important Factormentioning
confidence: 99%